2015
DOI: 10.1111/1742-6723.12340
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effectiveness of a revised clinical practice guideline for the pre‐hospital management of supraventricular tachycardia

Abstract: The revised CPG improved pre-hospital SVT reversion success. This expansion of practice has not demonstrated improvements to utilisation or effectiveness of the Valsalva manoeuvre. Adenosine is effective and safe for pre-hospital use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5. In cases where there has been inappropriate administration of adenosine, this had not been associated with adverse outcomes2 6 and, with training, inappropriate administration rates are reduced 7.…”
Section: Introductionmentioning
confidence: 99%
“…Small prospective studies have demonstrated that administration of adenosine in a community setting is safe2 3 and there is a good correlation between paramedics' interpretation of the ECG and that of physicians 4 5. In cases where there has been inappropriate administration of adenosine, this had not been associated with adverse outcomes2 6 and, with training, inappropriate administration rates are reduced 7.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate higher reversion rates than previously reported 3. However, given that the VM is a primary therapy used by emergency physicians (in hospital), paramedics (out of hospital) and patients (in their own home), there is some limitation to the practical generalisability of the MVM.…”
Section: Commentarymentioning
confidence: 56%
“…While controversial, reviews of these maneuvers suggest they have limited effectiveness, with the greatest utility being when they are initiated as close as possible to the start of the PSVT. [51][52][53] In evaluation of current treatments, etripamil appears to be as effective as the intravenous standard of care, with conversion rates of 85-90% for adenosine, 90% for verapamil, and 98% for verapamil using a slow infusion protocol. 8,42,52,54 Overall, etripamil has demonstrated a limited side effect profile, an equivalent efficacy to the standard of care, and the advantage of easy self-administration.…”
Section: Clinical Experiencesmentioning
confidence: 99%
“…[51][52][53] In evaluation of current treatments, etripamil appears to be as effective as the intravenous standard of care, with conversion rates of 85-90% for adenosine, 90% for verapamil, and 98% for verapamil using a slow infusion protocol. 8,42,52,54 Overall, etripamil has demonstrated a limited side effect profile, an equivalent efficacy to the standard of care, and the advantage of easy self-administration. Of note, there were 3 rare major adverse effects as well as minor delivery-related side effects seen in both the placebo control and experimental groups, such as congestion, lacrimation, and rhinorrhea.…”
Section: Clinical Experiencesmentioning
confidence: 99%